(untitled) (Revista Contexto & Saúde, 2024)
Objective: This study aimed to assess school environment factors associated with adherence to school meals among adolescents from Brazilian public schools. This is a cross-sectional study with data of 67.881 adolescents aged 11 to 19 years, students from public schools who participated in the 2015 National Adolescent School-based Health Survey (PeNSE). Methods: The dependent variable was the frequency of school meals consumption, classified as adherence (≥3x/week), unsatisfactory adherence (1-2x/week), and non-adherence (no day). Multilevel ordinal proportional odds regression was used to estimate the effect of individual variables and the school environment on school meals adherence. Results: Among the students evaluated, 31.3% adhered to school meals, 37.9% adhered to it unsatisfactorily, and 30.8% did not adhere to it. After adjusting for individual variables, greater adherence was observed among those who attended schools without a canteen (OR: 1.46; 95% CI: 1.35-1.57), without an alternative food sale outlet (OR: 1.29; 95% CI: 1.20-1.39), from the South (OR: 1.38; 95% CI: 1.22-1.56), Southeast (OR: 1.30; 95% CI: 1.16-1.46), and the Midwest (OR: 1.95; 95% CI: 1.75- 2.18), non-capitals (OR: 1.42; 95% CI: 1.33-1.52) and rural areas (OR: 1.41; 95% CI: 1.26-1.57). Conclusion: Factors of the school context and the school food environment, especially the presence of a canteen and an alternative food sale outlet, influence the adherence to school meals among Brazilian school adolescents.